Employee satisfaction in the telecommunications industry in Malaysia - Iridianathan, Caroline Maria; Wider, Walton; Abdullah, Meor Rashydan; Sam, Toong Hai; Vasudevan, Asokan; Daud, Siti Nurbaayah (Conscientia beam, 2022)
Following the COVID-19 pandemic, there has been a decline in employee satisfaction. It would appear that ensuring the contentment of one's workforce in their place of employment is the most significant obstacle that companies must overcome. Therefore, this study examined the effects of wages and welfare, relations with superiors, and learning and development on employee satisfaction in Malaysia. The study employed a cross-sectional design, and the research instruments were adapted from several prior studies. Employees working for a telecommunications company in Malaysia completed a total of 162 questionnaires online. The research hypotheses were analysed using SPSS Version 26.0. The findings show that although relations with superiors had a significant positive effect on employee satisfaction, learning and development had an even stronger positive effect. On the other hand, wages and welfare did not display a significant effect on employee satisfaction. This study makes a unique contribution to theoretical understanding by investigating these factors in the middle of the COVID-19 pandemic as intrinsic and extrinsic components impacting employee satisfaction. Additionally, this research gives corporate organisations vital insights to ensure they can maintain a competitive edge in their industry.